Thank You to Our Peer-Reviewers - The Editorial Team (Universitas Negeri Gorontalo, 2021)
There is currently much discussion and criticism about the peer review process and what form it should take moving forward. For Jambura Industrial Review, however, high-quality peer review is still at the heart of the academic publication process and is one of the means by which our academic editors promote scientific truth and knowledge, thereby safeguarding the integrity of the scientific literature. The thoughtful comments and recommendations and insightful guidance offered by our peer reviewers are essential parts of our editorial evaluations of submitted manuscripts. These reports help us to make informed decisions so that we can ensure that the research we publish in the journal is of the highest quality.Back to our peer reviewers of 2021, who so generously volunteered their time and expertise. We want to acknowledge your time and effort, and express our genuine gratitude for your contributions and support. To you all (listed in the PDF file below) – thank you.